An Analysis of Translation Techniques and Quality of Taboo Words in the Gran Torino Movie - Fitriansyah, Fiana (Jurnal Bahasa, Sastra, dan Studi Amerika, 2023)
The research aims to identify type and function of taboo words in the Gran Torino movie, to find out the techniques used in translating the taboo words, to examine the shift in type and function of the taboo words, and to evaluate the accuracy and the acceptability of the taboo words translation.This research uses a descriptive qualitative method. The data are taboo words in the Gran Torino movie in the form of an English script and its subtitle (Indonesian). The informants provided data of information about the translation techniques and quality through Focus Group Discussions (FGD).The findings show that there are total 270 data. There are 10 types of taboo words; body parts, sexual acts, ethnic insults, profanity, vulgarity, curse, scatology, animal names, ancestral allusion, and insulting references to perceived psychological, physical, or social deviations. There are four functions of taboo words; auxiliary, abusive, expletive, and humorous. 96% of data are type-shifted and 76% are function-shifted. There are five translation techniques found; reduction (43.7%), establishes equivalent (23%), explicitation (20%), adaptation (8.1%), implicitation (3.7%), discursive creation (0.7%), and literal translation (0.4%). The average accuracy score is 1.78 while the acceptability is 2.12. Therefore, the translation quality score is 1.92.